Synthesis of benzocarbazole isomer as a model study to determine the extend of byproduct formation of dibenzo[b,g]carbazole in the synthesis of dibenzocarbazole - Foo, KaiYu. (2009)
Development and applications of carbon nanotube has sparked a worldwide research into improving the properties of carbon nanotube (CNT) by functionalization. Dibenzocarbazole monomer was synthesized for the investigation of its polymer wrapping properties and binding strength to single wall carbon nanotube (SWNT). However, the synthesis methodologies of Suzuki coupling and ring closure reaction generated a byproduct of dibenzo[b,g]carbazole.